Metagenomic analysis reveals the abundance changes of bacterial communities and antibiotic resistance genes in the influent and effluent of hospital wastewater - Xu Jia; Jiaojiao Peng; Junhong Lv; Yuanting Li; Ziren Luo; Jing Xiang; Yaqin Hou; Qian Zheng; Bin Han (PLoS ONE, 2025)
The presence of substantial quantities of antibiotics and their metabolites in hospital wastewater can lead to the accumulation of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs). Research on the influent and effluent sewage of hospitals is crucial for understanding the effectiveness of wastewater treatment systems in inactivating ARB and ARGs. Key features of microbial communities and ARGs in influent and effluent wastewater – including taxonomic diversity and relative abundance – were assessed via metagenomic sequencing. The treatment process resulted in a reduction of the overall bacterial count in hospital wastewater. However, a notable increase in relative abundance was observed for three phyla, 16 genera, and 21 species post-treatment. Bacteria harboring ARGs were predominantly identified as belonging to Pseudomonadota and Bacillota . A total of 354 ARGs were detected in the influent, while 331 were identified in the effluent samples, with a general decrease in absolute abundance. Nevertheless, the relative abundance of certain ARGs, such as mphG , fosA8 , and soxR , was found to increase in the effluent across all samples. Seasonal fluctuations also played a role in the distribution of microbial communities and ARGs. These findings underscore the role of hospital wastewater treatment systems in reducing the discharge of ARB and ARGs into the environment, while also revealing potential shortcomings in the wastewater treatment process that necessitate further improvement for more effective removal of these ARGs.